Using Smartphone‐Based Support Groups to Promote Healthy Eating in Daily Life: A Randomised Trial. Issue 3 (25th September 2017) - Inauen, Jennifer; Bolger, Niall; Shrout, Patrick E.; Stadler, Gertraud; Amrein, Melanie; Rackow, Pamela; Scholz, Urte
Abstract : Background: Although many people intend to eat healthily, they often fail to do so. We report the first randomised trial testing whether smartphone‐based support groups can enhance healthy eating. Methods: Adults ( N = 203) were randomised to the support or control condition (information), and to one of two eating goals (increasing fruit and vegetable/decreasing unhealthy snack consumption). After baseline, participants received information on their assigned eating goal, and completed a 13‐day electronic diary. During Days 4–10, support participants were asked to support each other in achieving their eating goal in smartphone‐based groups. The primary outcome was daily servings of fruit/vegetables or unhealthy snacks. Maintenance of intervention effects was assessed on Days 11–13, and at 1‐month and 2‐month follow‐ups. Results: Support participants showed a gradual increase in healthy eating over time, and ate 1.4 fruits and vegetables more, 95% CI [0.3, 2.6], or 0.8 unhealthy snacks less, 95% CI [−1.4, −0.2] than controls on Day 10. Most effects were not maintained at follow‐ups. Conclusions: Smartphone‐based groups can promote fruit and vegetable consumption and decrease unhealthy snack intake. This study extends previous findings of the benefits of support groups, and sheds light on the temporal dynamics of behavior change.